Review: An integrated graphical tool for analysing impacts and services provided by livestock farming. (4th March 2019) - Ryschawy, J.; Dumont, B.; Therond, O.; Donnars, C.; Hendrickson, J.; Benoit, M.; Duru, M.
Abstract : Livestock farming is criticized for negatively impacting the environment, concerns about animal welfare and the impact of excessive meat consumption on human health. However, livestock farming provides other underappreciated and poorly communicated benefits to society in terms of employment, product quality, cultural landscapes and carbon storage by grasslands. Few attempts have been made so far to simultaneously consider the services and impacts provided by livestock production. Here, we propose an integrated graphical tool, called the 'barn' to explicitly summarize the synergies and trade-offs between services and impacts provided by livestock farming. It illustrates livestock farming interacting with its physical, economic and social environment along five interfaces: (i) Markets, (ii) Work and employment, (iii) Inputs, (iv) Environment and climate, (v) Social and cultural factors. This graphical tool was then applied by comparing two contrasting livestock production areas (high livestock density v. grassland-based), and the dominant v. a niche system within a crop-livestock area. We showed the barn could be used for cross-comparisons of services and impacts across livestock production areas, and for multi-level analysis of services and impacts of livestock farming within a given area. The barn graphically summarizes the ecological and socio-economic aspects of livestock farming by explicitly representing multiple services and impacts of different systems in a simple yet informative way. Information for the five interfaces relies on available quantitative assessments from the literature or data sets, and on expert-knowledge for more qualitative factors, such as social and cultural ones. The 'barn' can also inform local stakeholders or policy-makers about potential opportunities and threats to the future of livestock farming in specific production areas. It has already been used as a pedagogical tool for teaching the diversity of services and impacts of livestock systems across Europe and is currently developed as a serious game for encouraging knowledge exchange and sharing different viewpoints between stakeholders.